Extracellular Signal-Regulated Kinase Signaling in CD4-Expressing Cells Inhibits Osteochondromas - Wehenkel, Marie; Corr, Maripat; Guy, Clifford S.; Edwards, Benjamin A.; Castellaw, Ashley H.; Calabrese, Christopher; Pagès, Gilles; Pouysségur, Jacques; Vogel, Peter; McGargill, Maureen A. (Frontiers in Immunology, 2017)
Defects in cartilage homeostasis can give rise to various skeletal disorders including osteochondromas. Osteochondromas are benign bone tumors caused by excess accumulation of chondrocytes, the main cell type of cartilage. The extracellular-signal-regulated kinase (ERK) pathway is a major signaling node that functions within chondrocytes to regulate their growth and differentiation. However, it is not known whether the ERK pathway in other cell types regulates cartilage homeostasis. We show here that mice with a germline deficiency of Erk1 and a conditional deletion of Erk2 in cells that express CD4, or expressed CD4 at one point in development, unexpectedly developed bone deformities. The bone lesions were due to neoplastic outgrowths of chondrocytes and disordered growth plates, similar to tumors observed in the human disease, osteochondromatosis. Chondrocyte accumulation was not due to deletion of Erk2 in the T cells. Rather, CD4cre was expressed in cell types other than T cells, including a small fraction of chondrocytes. Surprisingly, the removal of T cells accelerated osteochondroma formation and enhanced disease severity. These data show for the first time that T cells impact the growth of osteochondromas, and describe a novel model to study cartilage homeostasis and osteochondroma formation.